The intergenerational transmission of opioid dependence: Evidence from administrative data - Alexander Ahammer; Martin Halla (Johannes Kepler University of Linz, Department of Economics, 2021)
To address the opioid crisis, it is crucial to understand its origins. We provide descriptive evidence for the intergenerational transmission of opioid dependence. Our analysis is based on administrative data covering the universe of Austrian births from 1984 to 1990. We consider prescription opioids and a new proxy for addiction to illicit opioids. We find that, if at least one parent is using illicit opioids, the likelihood of the child using increases from 1.1 to 7.1%. For prescription opioids, we observe an increase from 4.6 to 7.7%. Both associations are stable and do not change when controlling for environmental variables.
Keywords: I12; I14; I18; J62; 330; Opioids; prescription opioids; illicit opioids; heroin; addiction; drug abuse; intergenerational transmission; intergenerational correlation